Serum Fasting Non-esterified Fatty Acids and Carotid Artery Intima-Media Thickness in Older Adults: The Cardiovascular Health Study. (7th June 2021) - Huang, Neil; Bůžková, Petra; Matthan, Nirupa; Djoussé, Luc; Kizer, Jorge; Mukamal, Kenneth; Polak, Joseph; Lichtenstein, Alice
Abstract: Objectives: Carotid artery intima-media thickness (CIMT) has been used as an early indicator of subclinical atherosclerosis. Multiple studies have identified significant associations between plasma total non-esterified fatty acid (NEFA) concentrations and risk factors associated with subclinical atherosclerosis. However, the relationship between CIMT and serum NEFA is less clear. We hypothesized fasting serum total, individual saturated, and trans NEFA are positively associated with, and individual monounsaturated, n-6 polyunsaturated (PUFA) and n-3 PUFA NEFA are inversely associated with, CIMT. Methods: We investigated the associations between fasting serum NEFA, and CIMT assessed in 1998–1999 among Cardiovascular Health Study (CHS) participants ( N = 1, 569) not taking anti-diabetic medication. A total of 35 individual NEFAs were measured in stored specimens from 1996–1997 using gas chromatography. CIMT was determined using ultrasound images, and was defined as the sum of the maximum common CIMT at the far wall divided by its standard deviation (SD) and the maximum internal CIMT at the far wall divided by its SD. At baseline, mean age was 77.3 ± 4.2, body mass index (BMI) was 26.8 ± 4.3 and 64% were female. Associations were assessed by linear regression, with adjustments for other individual NEFAs, age, sex, race, field center, education, smoking, BMI, physical activity, alcohol consumption, eGFR, serum albumin, hyperglycemia, hypertension, use of anti-hypertensive, statin, and other lipid-lowering drugs. Results: In adjusted models per SD increment, linoelaidic acid ( trans 18:2) was positively associated with CIMT [β (95% confidence interval): 10.4 (0.99, 19.8), P = 0.03], and α-linolenic acid (18:3n-3) was marginally associated with lower CIMT [−21.2 (−42.6, 0.2), P = 0.05]. No significant associations were observed between total NEFAs or any other individual NEFAs (SFA, MUFA, and n-6 PUFA) and CIMT. Conclusions: In this large community-based cohort of older adults, higher concentration of linoelaidic acid was positively associated with CIMT, suggesting the importance of partially hydrogenated fat in the development of subclinical atherosclerosis in older adults. Overall, however, serum fasting NEFAs were largely unrelated to subclinical atherosclerosis in CHS participants. Funding Sources: NIH, NHLBI, USDA.